Correlation of p16 immunohistochemistry in FNA biopsies with corresponding tissue specimens in HPV‐related squamous cell carcinomas of the oropharynx. Issue 12 (4th August 2015) - Jalaly, Jalal B.; Lewis, James S.; Collins, Brian T.; Wu, Xingyong; Ma, Xiao‐Jun; Luo, Yuling; Bernadt, Cory T.
Abstract : BACKGROUND: Human papillomavirus (HPV)‐related oropharyngeal squamous cell carcinoma (SCC) is a unique form of carcinoma that is important to identify for prognosis and treatment. Immunohistochemistry (IHC) for p16 (also known as cyclin‐dependent kinase inhibitor 2A, multiple tumor suppressor 1) is used as a surrogate marker for transcriptionally active, high‐risk HPV. The primary objective of this study was to correlate p16 IHC of cell blocks from fine‐needle aspirations (FNAs) with surgical pathology specimens of HPV‐related oropharyngeal SCC. METHODS: In total, 48 patients who had a diagnosis of oropharyngeal or nonoropharyngeal SCC and also had an FNA that demonstrated metastatic SCC with available cell block material were identified. IHC for p16 was evaluated on both FNA cell blocks and surgical pathology specimens. In situ hybridization for high‐risk HPV messenger RNA was performed on 31 of the FNA cell blocks. RESULTS: Although partial p16 staining was observed in the majority of cell blocks, there was concordance in 47 of 48 FNAs (98%) with surgical pathology specimens when strong positive p16 staining of at least 15% of tumor cells in FNA cell block material was present. In addition, high‐risk HPV RNA in situ hybridization demonstrated a high correlation with p16 staining in surgical pathology specimens (96%) and FNAs (93%). CONCLUSIONS: There was excellent correlation between p16 IHC of FNA cell blocks and surgical pathology specimens using a cutoff of at least 15% positive staining in cell blocks. The recommended threshold (70% positive staining) for surgical pathology specimens may yield a high rate of false‐negative results if applied to FNA cell blocks. Cancer (Cancer Cytopathol) 2015;123:723–731. © 2015 American Cancer Society . Abstract : An evaluation of p16 immunohistochemistry of cell blocks from fine‐needle aspiration biopsies compared with surgical pathology specimens of human papillomavirus‐related oropharyngeal squamous cell carcinoma is reported. There is excellent correlation between the 2 methods using a cutoff of at least 15% focal confluent staining in cell blocks.